2016
DOI: 10.1371/journal.pone.0153696
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Piperacillin-Tazobactam versus Carbapenems in the Treatment of Bacteraemia Due to Extended-Spectrum Beta-Lactamase-Producing Enterobacteriaceae

Abstract: Extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae are a common cause of bacteraemia in endemic countries and may be associated with high mortality; carbapenems are considered the drug of choice. Limited data suggest piperacillin-tazobactam could be equally effective. We aimed to compare 30-day mortality of patients treated empirically with piperacillin-tazobactam versus a carbapenem in a multi-centre retrospective cohort study in Singapore. Only patients with active empiric monotherapy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 33 publications
5
70
0
2
Order By: Relevance
“…Finally, Ng and colleagues evaluated 30-day mortality comparing empiric PTZ and carbapenem in 151 patients with presumed ESBL bloodstream infections. Thirty-day mortality was no different between the groups [53]. As with previous studies that resulted in similar outcomes between the treatment groups, a minority of patients were in the ICU (<10%), the majority of patients were infected with E. coli bacteremia, and almost 70% of patients had urinary or biliary sources of bacteremia.…”
Section: Piperacillin-tazobactamsupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, Ng and colleagues evaluated 30-day mortality comparing empiric PTZ and carbapenem in 151 patients with presumed ESBL bloodstream infections. Thirty-day mortality was no different between the groups [53]. As with previous studies that resulted in similar outcomes between the treatment groups, a minority of patients were in the ICU (<10%), the majority of patients were infected with E. coli bacteremia, and almost 70% of patients had urinary or biliary sources of bacteremia.…”
Section: Piperacillin-tazobactamsupporting
confidence: 75%
“…Existing observational data have indicated contradictory results between outcomes of patients receiving PTZ and carbapenems for the treatment of ESBL infections (Table 5) [8,47,[48][49][50][51][52][53][54]. Rodriguez-Baňo and colleagues provided some of the earliest robust data evaluating β-lactam-β-lactamase inhibitors (βL-βLIs) and carbapenems for the treatment of ESBL bacteremia by conducting a post hoc observational study of Spanish patients from 6 cohorts [47].…”
Section: Piperacillin-tazobactammentioning
confidence: 99%
“…Of interest, we identifi ed high empiric use of carbapenem/quinolone drug classes despite low identifi cation of ESBL on the BC-GN result at the Baylor Irving site. Although carbapenems are active in this setting, these high-cost agents should be reserved for the additional coverage of drug-resistant organisms (13,14). Th e outcome of this study will allow concentration of antimicrobial stewardship eff orts at this site.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly worrisome in a scenario in which carbapenem-resistant Enterobacteriaceae (CRE) are spreading rapidly and are adversely compromising patients' outcomes (7)(8)(9)(10)(11)(12). While recent investigations have suggested that ␤-lactam/␤-lactamase inhibitors (BLBLIs) may be reliable options for the treatment of BSI due to ESBL-producing Gram-negative bacilli (ESBL-GNB), especially in nonimmunocompromised patients (13)(14)(15)(16)(17)(18)(19), other studies have found contrasting data (20,21). To date, the efficacy of BLBLIs for the treatment of BSI due to ESBL-GNB in high-risk hematological patients has not been established.…”
mentioning
confidence: 99%